PERLINDUNGAN HUKUM BAGI KAUM DISABILITAS DALAM PEMILU DI INDONESIA - Arie Sulistyoko; Bahran, Fauziyah Hayati, Hayatun Na’imah, Anwar Hafidzi (JOURNAL OF LAW AND NATION, 2022)
Like humans in general, people with disabilities also have rights in life, one of which is the right to vote. People with disabilities can also vote or participate in elections, like humans in general, people with disabilities are also entitled to get election socialization, special data collection, special polling stations, special ballots, and also have the right to get a companion. Problems begin to arise when there is no protection for people with disabilities related to secret ballots. The second is how the government's efforts to fulfill political rights for people with disabilities. The purpose of this research is to find out about legal protection for people with disabilities related to secret ballots and to find out the views of positive law and Islamic law on political rights for people with disabilities. This research is normative juridical legal research using conceptual approaches and statutory approaches. The results of this study found that the government is obliged to provide legal protection for people with disabilities in elections. The government is obliged to provide different facilities for people with disabilities related to secret ballots. Islam does not differentiate them among other humans. Because what distinguishes them is only the level of piety to God Almighty. Islam is very concerned about their rights and obligations. Legislation also regulates the protection of people with disabilities in their political rights, such as Article 28D paragraph (1) of the 1945 Constitution, Article 4 paragraph (1) of Law 8/2016 and Article 43 of Law Number 39 of 1999 concerning Human Rights.